PERILAKU KONSUMTIF: STUDI KUANTITATIF DESKRIPTIF MASYARAKAT DI KABUPATEN KOTABARU - Paujiah, Paujiah; Ariani, Lita (Lafadz Jaya Publisher, 2023)
The purpose of this study is to be able to provide an overview of consumptive behavior in the community in Kotabaru District. This research method uses a quantitative approach with descriptive research methods. Sampling in this study is using incidental sampling technique. The subjects of this study were people who shopped for more than IDR 100,000 per day for 50 subjects. The results obtained from this study indicate that the majority of people in Kotabaru District, South Kalimantan, have consumptive behavior in the moderate category.